THE ROLE OF PARENTS IN THE CHILD'S SELF-AWARENESS IN THE FAMILY (Scientific journal of the Fergana State University, 2024)
In this article, the role of parents in the self-awareness of children of primary school age in the family is highlighted on the basis of research tests. It covers emotional intimacy, boundaries of family relationships, decision-making, family roles, family rules, and family organization scales.